Chemical Design Rules for Non‐Fullerene Acceptors in Organic Solar Cells. Issue 44 (8th October 2021) - Markina, Anastasia; Lin, Kun‐Han; Liu, Wenlan; Poelking, Carl; Firdaus, Yuliar; Villalva, Diego Rosas; Khan, Jafar I.; Paleti, Sri H. K.; Harrison, George T.; Gorenflot, Julien; Zhang, Weimin; De Wolf, Stefaan; et al.
Abstract: Efficiencies of organic solar cells have practically doubled since the development of non‐fullerene acceptors (NFAs). However, generic chemical design rules for donor‐NFA combinations are still needed. Such rules are proposed by analyzing inhomogeneous electrostatic fields at the donor–acceptor interface. It is shown that an acceptor–donor–acceptor molecular architecture, and molecular alignment parallel to the interface, results in energy level bending that destabilizes the charge transfer state, thus promoting its dissociation into free charges. By analyzing a series of PCE10:NFA solar cells, with NFAs including Y6, IEICO, and ITIC, as well as their halogenated derivatives, it is suggested that the molecular quadrupole moment of ≈75 Debye Å balances the losses in the open circuit voltage and gains in charge generation efficiency. Abstract : Energy level bending at the donor‐acceptor interface of a solar cell due to the acceptor–donor–acceptor molecular architecture suggests the optimal molecular quadrupole moment of ca. 75 Debye Å for the acceptor molecule.